Development on Orthotics Insole for Flat Feet Focusing on Sport Usage Evaluated by Electromyography - Ahmad, Umi Hayati; Ab Rahman, Mohd Hidayat; Yee Sin, Lum; Maidin, Nurul Ain; Wakhi Anuar, Nur Farah Bazilah (International Journal of Integrated Engineering, 2019)
Running is a method of terrestrial locomotion allowing humans to move rapidly on foot, which related to the movement of lower limb. But for flat feet, running or walking for a long period will give them a high-risk associate with a foot pain. In order to reduce the foot pain, an arch orthotics insole is advised to be wore by the flat feet. This paper provides an extensive study on orthotics insole focusing on sport usage for flat feet. For this silicon rubber Orthotics Insole is designed with sufficient arch support, sufficient thickness, metatarsal pad, heel pad, heel cup and ergonomics dimension specification. The objectives of this research are to design and improve the efficiency of orthotics insole for flat feet focusing on sport usage. Both new orthotics insole and existing insole will be evaluated by using electromyography (EMG) that will record the electrical potential which generated by muscle cells. The output of time domain feature and frequency domain feature for both insoles will be analyzed and compared. This Orthotics Sport Insole ideal to be used by flat feet especially during their sport activity specifically running in order to reduce muscle pain to prevent injuries.